Discourse on moving the new capital city in East Kalimantan Province a political economy perspective - Syifa Izdihar Firdausa Asfianur; Suswanta Suswanta; Ridho Al-Hamdi; Zuly Qodir (Faculty of Social and Political Science, Universitas Airlangga, 2023)
This paper aimed to examine the discourse on moving the new state capital in Indonesia. The relocation of the national capital city was highly controversial, with many significant indicators of displacement according to the level of interest in it. The new capital city of Indonesia will be located in Kutai Kartanegara Regency and Penajam Paser Utara Regency. This study looks at the discourse of moving the national capital from a political economy perspective. This study uses qualitative research methods, with a literature review and NVIVO12 analysis. The discourse on moving the state capital explained many interests of the government and people in East Kalimantan Province. This discourse has pros from a political and economic point of view considering the benefits it could bring and cons from a judicial and academic perspective on the reasons and urgency behind relocating the state capital. It is assumed that the development of the National Capital will be evenly distributed, although in fact the management of urban planning has not been carried out properly. This study recommends that a more in-depth study is needed so that the relocation of the capital can provide greater benefits to the people of Indonesia in accordance with national goals.